Evaluation of Language Disorder in Children - A Case Study of Gboko Central Primary School Pupils, Benue State, Nigeria (Journal of Natural Language and Linguistics, 2025)
Language disorders or language impairments are disorders that involve the processing of linguistic information. Problems that may be experienced can involve grammar (syntax and/or morphology), semantics (meaning), or other aspects of language. These problems may be receptive (involving impaired language comprehension), expressive (involving language production), or a combination of both. The fact that some children fail to acquire language abilities is the central concern of this research and is being identified as the major problem and subject of investigation in this study. The study adopts Chomsky’s theory of Universal Grammar. The interesting principle of this theory that makes it suitable for being a framework for this study is that it posits that children go through stages of language development, and the “mistakes” they make during this time only reveal their development stage, but during their maturation, they are resistant to correction. The evaluation was done in the semantic phonological and syntactic areas of language, including stuttering analysis. The information gathered shows that children are affected by various language disorders and degrees. The research suggests that parents should be sensitized to examine the language acquisition stages of their children so as to identify any disorder early as this is important for intervention and remedy. Although this school is not a special kind for this defect, the study is carried out to ascertain language disorder among these pupils.